ALTERNATIVE MODEL FOR PUTTING INDONESIAN YOUNG DIGITAL TALENT IN BUSINESS - Sudarmaji, Eka; Munirah, Mira (Review of Management and Entrepreneurship, 2019)
This paper explores the experiential teaching of ‘work & innovation-based’ learning entrepreneurship through a Lean Startup Methodology (LSM). The LSM is a practical framework for entrepreneurship students to test whether their new innovation idea meets customers’ expectations. The iterative approach, according to LSM, to develop new innovation- based products is used and LSM was compiled into a number of principles. The students have been forced to implement LSM in early-phase ventures. This study investigated several factors that influenced prospective young entrepreneurs in Entrepreneurship Education within students, based on a sample of 225 university students. The research model used the ‘Non-Equivalent Groups Design’ (NEGD) framework for both ‘observed group’ and ‘control group’. The results of this study showed that “Perceived Desirability” and “Perceived Feasibility” have impacted on Entrepreneurial Intentions in an integrated environment of higher education. The descriptive statistic and MANOVA Analysis were used to analyze the Entrepreneurial Intentions of young digital talents.